“Who Killed Happy Valley?”: Air Pollution and the Birth of an Ontario Ghost Town, 1969-1974 - Miller, Scott (Ontario History)

(untitled) (The Ontario Historical Society, 2020)
While there are many ghost towns scattered across Ontario, the history of Happy Valley, located in the Sudbury area, is unique. For decades, this hamlet of about one hundred people suffered from air pollution produced by the nearby operations of Falconbridge Nickel Mines Limited (FNM). After years of pressure to do something about this situation, in the early 1970s the Ontario government facilitated the abandonment of Happy Valley in cooperation with the Regional Municipality of Sudbury and FNM. The controversial decision made headlines; it was the first instance in which the provincial government financed the relocation of an entire community because of air pollution. This article highlights how all of these factors shaped the Happy Valley affair and demonstrates how the government’s resolution was justified given the circumstances.